Influence of aqueous extract of Agaricus blazei on rat liver toxicity induced by different doses of diethylnitrosamine - Barbisan, L. F.; Miyamoto, M.; Scolastici, C.; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, L. R.; Eira, A. F.; de Camargo, JLV (Elsevier B.V., 2002)
The modifying potential of prior administration of an aqueous extract of the mushroom Agaricus blazei Murrill (Agaricaceae) (Ab) on hepatotoxicity induced by different doses of diethylnitrosamine (DEN) in male Wistar rats was evaluated. During 2 weeks, animals of groups G3 (Ab+DEN50), G5 (Ab+DEN100), G7 (Ab+DEN200), and G8 (Ab-treated) were treated with the A. blazei through drinking water. After this period, groups G2 (DEN50), G3 (Ab+DEN50), G4 (DEN100) G5 (Ab+DEN100), G6 (DEN200), and G7 (Ab+DEN200) were given a single i.p. injection of 50, 100 and 200 mg/kg of DEN, respectively, while groups G1 (nontreated) and G8 (Ab-treated) were treated with 0.9% NaCl only. All animals were killed 48 h after DEN or NaCl treatments. The hepatocyte replication rate was estimated by the index of the proliferating cell nuclear antigen (PCNA) positive hepatocytes and the appearance of putative preneoplastic hepatocytes through expression of the enzyme glutathione S-transferase placental form (GSTP). After DEN-treatment, ALT levels, PCNA labeling index, and the number of GST-P positive hepatocytes were lower in rats that received A. blazei treatment and were exposed to 100 mg/kg of DEN. Our findings suggest that previous treatment with A. blazei exerts a hepatoprotective effect on both liver toxicity and hepatocarcinogenesis process induced by a moderately toxic dose of DEN. (C) 2002 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: Agaricus blazei; Murrill; chemoprotection; hepatoprotection; liver toxicity; diethylnitrosamine